PENGUJIAN CELAH KEAMANAN MENGGUNAKAN METODE OWASP WEB SECURITY TESTING GUIDE (WSTG) PADA WEBSITE XYZ - Albestty Islamyati Rafeli (2022)
XYZ as a research website, of course, has a lot of sensitive data, such as personal data of users, both researchers and respondents, and data from research results. This data is vulnerable to data leakage or being stolen and misused by irresponsible people and harming many parties. Penetration Testing is a way to simulate a method that would be used by an attacker or irresponsible person to be able to illegally access data into the system. WSTG stands for Web Security Testing Guide, which is a Cyber security testing project guide, especially in the field of web application developers and professional security. In this study, seven techniques were carried out, namely Information gathering, Configuration and Deployment Management Testing, Identity Management Testing, Input Validation Testing, Testing For Error Handling, Business Logic Testing and Client Side Testing. The technique is applied to the XYZ website so that it gets a vulnerability from the XYZ website. In this study, eight vulnerabilities were found on the XYZ website. After a thorough risk assessment, the risk of the vulnerabilities on the XYZ website is included in the medium category.